(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Approximately 15% of couples are infertile. Male infertility plays an important role in about half of these couples. This study has been done to determine whether sperm morphology and motility do really affect sperm count or spermatogenesis and at the same time causes a problem with fertility. Objectives: The objective of this study was to evaluate a males inability to cause pregnancy in a fertile female. Materials and Methods: This is a prospective study of 100 diagnosed infertile and subfertile couples in the age group of 23-58 yrs old male. They were selected from 01 March 2013 to 28 Feb 2014 undergoing treatment for infertility in Dhaka CMH. On the basis of sperm count the cases were grouped as follows: Normozoospermia, oligozoospermia & Azoospermia. Semen analysis was done in all the cases and the results were described with arithmetic mean and standard deviation. Results: Normozoospermia: Mean and SD of sperm count, sperm abnormality, sperm motility are 65.98± 5.05, 24.44±1.57 and 45.5±2.94 respectively; Oligozoospermia: Mean and SD of sperm count, sperm abnormality, sperm motility are 7.74±1.23, 41.1±3.78, 14.54±2.77 respectively; Azoospermia: Mean and SD of sperm count, sperm abnormality, sperm motility are absent. Conclusion: Here data statistically showed person with normozoospermia having good sperm morphology and motility than oligozoospermia and azoospermic subjects thereby causing male infertility which is responsible for hindrance in achieving pregnancy clinically. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 50-53